2016
DOI: 10.4103/0377-4929.174818
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of mediastinal masses operated in a tertiary care hospital in Eastern India in 3 years with special reference to thymoma

Abstract: This study reflects the incidence of different mediastinal masses in West Bengal with their clinicopathologic correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
4
11
0
Order By: Relevance
“…1,7,8,11 In the mediastinum the majority of the lesions were seen in the anterior mediastinum similar to other studies. 16,17 In the present study haematolymphoid malignancy was the most type of malignancy in the mediastinal region. We did not have a single case of thymoma which was the most common mediastinal lesion in the other studies.…”
Section: Non Neoplastic Lesionssupporting
confidence: 49%
“…1,7,8,11 In the mediastinum the majority of the lesions were seen in the anterior mediastinum similar to other studies. 16,17 In the present study haematolymphoid malignancy was the most type of malignancy in the mediastinal region. We did not have a single case of thymoma which was the most common mediastinal lesion in the other studies.…”
Section: Non Neoplastic Lesionssupporting
confidence: 49%
“…The peak age of these lesions were in the 4 th and 5 th decades and they had an approximate M: F ratio of 1: 1. This was in concordance with the studies conducted independently by Dasgupta et al and Shrivastava et al 4,5 In this study 66% (103) of the lesions were found in the anterior mediastinum, 12% (33) in the middle mediastinum, 8% (13) in the posterior mediastinum and 5% (8) in the superior mediastinum. A similar study by Sharma et al showed 36.7% involvement of the anterior compartment followed by middle (33%) and posterior (30%).…”
Section: Discussionsupporting
confidence: 93%
“…Age distribution of all these cases was between 04 -70 yrs. [1][2][3][4][5][6][7][8][9][10][11][12] Out of total 43 cases we encountered 39 cases (90.60 %) were in adult age group (>16 yrs.) and the mean age in adults was (47.7 yrs.).…”
Section: Resultsmentioning
confidence: 99%